PEGylation enables subcutaneously administered nanoparticles to induce antigen-specific immune tolerance - Li, Peter Y. (J Control Release, 2021)
The development of nanomaterials to induce antigen-specific immune tolerance has shown promise for treating autoimmune diseases. While PEGylation has been widely used to reduce host immune responses to nanomaterials, its tolerogenic potential has not been reported. Here, we report for the first time that a subcutaneous injection of PEGylated poly(lactide-co-glycolide) (PLGA) nanoparticles containing auto-antigen peptide MOG(35–55) without any tolerogenic drugs is sufficient to dramatically ameliorate symptoms after disease onset in an antigen-specific manner in a mouse model of multiple sclerosis. Neither free MOG(35–55) nor particles without PEG exhibit this efficacy. Interestingly, mechanistic studies indicate that PEGylation of nanoparticles does not reduce dendritic cell activation through direct nanoparticle-cell interactions. Instead, PEGylated nanoparticles induce lower complement activation, neutrophil recruitment, and co-stimulatory molecule expression on dendritic cells around the injection sites than non-PEGylated PLGA nanoparticles, creating a more tolerogenic microenvironment in vivo. We further demonstrate that the locally recruited dendritic cells traffic to lymphoid organs to induce T cell tolerance. These results highlight the critical role of surface properties of nanomaterials in inducing immune tolerance via subcutaneous administration.